2020
DOI: 10.1523/jneurosci.2091-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiological Basis of the Trial-Wise and Cumulative Ventriloquism Aftereffects

Abstract: Our senses often receive conflicting multisensory information, which our brain reconciles by adaptive recalibration. A classic example is the ventriloquism aftereffect, which emerges following both cumulative (long-term) and trial-wise exposure to spatially discrepant multisensory stimuli. Despite the importance of such adaptive mechanisms for interacting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 68 publications
4
44
0
Order By: Relevance
“…We hence directly compared the magnitude of the aftereffect biases obtained here to data obtained in similar versions of this task in our previous work. To this end we reanalysed the data from a previous EEG study (Park & Kayser, 2021) (n=19), a study manipulating time delays in between trials (n=41) or introducing a mask between AV and A trials (n=44)(Park & Kayser, 2020) and a dataset obtained in a study comparing young and older participants (n=22; younger participants only) (Park et al, 2021). These paradigms differed in their number (using 9, 5, 9 and 9 levels respectively) or range of spatial discrepancies used (34°, 24°, 32° and 32°).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We hence directly compared the magnitude of the aftereffect biases obtained here to data obtained in similar versions of this task in our previous work. To this end we reanalysed the data from a previous EEG study (Park & Kayser, 2021) (n=19), a study manipulating time delays in between trials (n=41) or introducing a mask between AV and A trials (n=44)(Park & Kayser, 2020) and a dataset obtained in a study comparing young and older participants (n=22; younger participants only) (Park et al, 2021). These paradigms differed in their number (using 9, 5, 9 and 9 levels respectively) or range of spatial discrepancies used (34°, 24°, 32° and 32°).…”
Section: Resultsmentioning
confidence: 99%
“…This finding has interesting implications for the discussion of computational underpinnings of the aftereffect. Previous experiments have shown that the aftereffect can emerge independently on an immediate (trial-by-trial) scale and over cumulative long-term exposure (Bruns & Röder, 2015, 2019; Park & Kayser, 2021; Wozny & Shams, 2011b). Previous work has speculated that the immediate aftereffect may be directly related to the integration in the preceding trial, whereby the (implicit) judgement about a putative causal relation between two sensory cues moulds the recalibration process (Badde et al, 2020; Bruns & Röder, 2015; Noppeney, 2021; Park & Kayser, 2019; Rohlf et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations